Healthcare resource utilization and cost in dementia: are there differences between patients screened positive for dementia with and those without a formal diagnosis of dementia in primary care in Germany? – ERRATUM. (March 2016) - Michalowsky, Bernhard; Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Wucherer, Diana; Hoffmann, Wolfgang; Flessa, Steffen
Abstract : In the above mentioned article by Michalowsky et al., Johannes Hertel was mistakenly omitted from the authorship list. This error has been corrected in the print, PDF and HTML versions of the original article.